Malreduction of syndesmosis injury associated with malleolar ankle fracture can be avoided using Weber's three indexes in the mortise view. Issue 4 (April 2017) - Futamura, Kentaro; Baba, Tomonori; Mogami, Atsuhiko; Morohashi, Itaru; Kanda, Akio; Obayashi, Osamu; Sato, Kazuo; Ueda, Yasuhisa; Kurata, Yoshiaki; Tsuji, Hideki; Kaneko, Kazuo
Abstract: Purpose: Malalignment of syndesmosis is generally associated with a poor outcome, yet occurs at a high rate in malleolar ankle fractures. In this study, we examine whether malreduction of syndesmosis injury associated with malleolar ankle fracture can be avoided using Weber's three indexes in the mortise view. Materials and methods: Of 156 patients with malleolar ankle fracture who underwent surgery from December 2012 to March 2016 at two medical facilities, 24 patients who received syndesmotic screw fixation were included in the study. Fractures were Danis–Weber types B and C in 8 (8/134, 6.0%) and 16 (16/22, 72.7%) patients, respectively. Using axial computed tomography (CT), we calculated the difference between injured and non-injured sides for each of three parameters: tibiofibular clear space (TFCS), anterior tibiofibular interval (ATF), and fibular rotation ( θ fib ). Malreduction was diagnosed if one or more of the three parameters had an abnormal value. Weber's three indexes in the mortise view on the injured side were used to determine whether reduction of syndesmosis was performed successfully. Consistency between the evaluation of reduction of syndesmosis in axial CT images and reevaluation of mortise views was examined by calculation of sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results: The rate of malreduction of syndesmosis in axial CT images was 29.2% (7/24). Re-evaluation in the mortise view confirmed malreduction of syndesmosis in six of the seven subjects, all of whom also had malreduction based on axial CT images. The one subject in whom malreduction could not be detected in a mortise view showed an abnormal value only for ATF. Use of the mortise view for perioperative diagnosis had a sensitivity of 0.857, specificity of 1.000, PPV of 1.000, and NPV of 0.944. Conclusion: The results of our study show that malreduction of syndesmosis can be avoided by careful interpretation of intraoperative perspective mortise views based on Weber's three indexes. To increase the diagnostic accuracy further, it is important to detect anteroposterior deviation of the fibula in intraoperative lateral views.